Cumulative Carbon Emissions and Climate Change: Has the Economics of Climate Policies Lost Contact with the Physics? - Rhys, J (Oxford Institute for Energy Studies, 2011)
Carbon dioxide (CO2) emissions are essentially cumulative in character; but much of the economic analysis and policy making in relation to the mitigation of CO2 emissions fails to reflect fully this fundamental feature of any analysis of the impact of emissions on climate. The cumulative and irreversible nature of CO2 emissions implies that a significantly heavier weight should attach to current as opposed to future emissions. Unfortunately current application of market-based approaches to limiting carbon emissions delivers a contradictory message, with the price of current emissions being very low but with a prospect of rapid rises in the future. This inconsistency has the potential to create major distortions in policy and is likely to be seriously sub-optimal. Similar criticisms can be levelled at policies or climate negotiations based on individual year targets rather than cumulative emissions. Policy making needs to redress this imbalance. Focus on the cumulative nature of CO2 also strengthens the case for urgency and leads to more recognition of the positive option value of early action on emissions.